Species-level microbiota of ticks and fleas from Marmota himalayana in the Qinghai-Tibet Plateau - Dong, Lingzhi; Li, Yaben; Yang, Caixin; Gong, Jian; Zhu, Wentao; Huang, Yuyuan; Kong, Mimi; Zhao, Lijun; Wang, Feifei; Lu, Shan; Pu, Ji; Yang, Jing (Frontiers in Microbiology, 2023)
Ticks and fleas, as blood-sucking arthropods, carry and transmit various zoonotic diseases. In the natural plague foci of China, monitoring of Yersinia pestis has been continuously conducted in Marmota himalayana and other host animals, whereas other pathogens carried by vectors are rarely concerned in Qinghai-Tibet Plateau. In this study, we investigated the microbiota of ticks and fleas sampling from M. himalayana in Qinghai-Tibet Plateau, China. By metataxonomic approach based on full-length 16S rDNA amplicon sequencing and operational phylogenetic unit (OPU) analyses, we described microbiota community of ticks and fleas at the species-level, annotated 1250 OPUs in ticks, including 556 known species and 492 potentially new species, accounting for 48.50% and 41.71% of the total reads in ticks, respectively. A total of 689 OPUs were detected in fleas, consisting of 277 known species (40.62% of the total reads in fleas) and 294 potentially new species (56.88%). At the dominant species categories, we detected the Anaplasma phagocytophilum (OPU 421) and potentially pathogenic new species of Wolbachia, Ehrlichia, Rickettsia, and Bartonella. By shotgun sequencing, we obtained ten metagenomic assembled genomes (MAGs) from vector samples, including a known species (Providencia heimbachae DFT2), and six new species affiliated to four known genera, ie., Wolbachia, Mumia, Bartonella, and Anaplasma. By the phylogenetic analyses based on full-length 16S rRNA genes and core genes, we identified that ticks harbored pathogenic A. phagocytophilum, and these potentially pathogenic novel species were most close to Ehrlichia muris, Ehrlichia muris subsp. eauclairensis, Bartonella rochalimae, and Rickettsia limoniae, respectively. The findings of the study have advanced our understanding of the potential pathogen groups of vectors in marmot in the Qinghai-Tibet Plateau.